Planning and development in Ernesto Che Guevara’ thinking (Islas, 2021)
This article analyzes Che Guevara’s thoughts on economic development, as well as the policies that can favor it. An important aspect is the one related to socialist planning and its bonds with development.
Keywords: socialism; development; underdevelopment; planning